Effect of demulsification of oil-in-water emulsion in cationic condition using Graphene oxide: article - Yahya, Muhammad Ikhmal; Dollah, Aqilah (2018)
Graphene oxide (GO) is an amphiphilic material capable of breaking oil-in-water emulsion at room temperature. Chemical demulsification are widely being used in the industry to treat oil-in-water emulsion which involves the use of chemical additives to rapidly enhance the emulsion breaking process. Hummer's method was used and successfully synthesized graphene oxide from graphite powder through strong oxidation process. Characterization of the GO produced was done using FTIR and XRD The performance of GO on separation of cationic surfactant stabilized emulsion was assessed experimentally. Results shows that GO successfully improves the demulsification process even under acidic condition but decrease in performance under alkaline condition.